Reconfigurable circularly polarized cross-dipole antenna with a near-field resonant parasitic element - Ta, Son Xuat; Park, Ikmo; Ziolkowski, Richard W. (IET Conference Publications, 2018)
This paper presents a polarization switchable circularly polarized (CP) antenna that consists of a compact single-feed crossed dipole loaded with a near-field resonant parasitic (NFRP) element. This antenna is placed above a metallic reflector to enhance its gain and broadside radiation pattern. A meander line with an arrowhead-shaped ending was applied to all arms of the crossed dipole and NFRP elements for compactness. By adjusting the end size of the NFRP element, the antenna was capable of switching its polarization from right-hand circular polarization to left-hand circular polarization and vice versa. The reconfigurability is realized by controlling the ON/OFF states of 8 PIN-diodes, which are inserted into the arrowhead endings of the NFRP element. For the RHCP mode, the antenna yields a |S11| < -10 dB bandwidth of 1.465-1.665 GHz and a 3-dB axial ratio (AR) bandwidth of 1.535-1.590 GHz. For the LHCP mode, the antenna yields a |S11| < -10 dB bandwidth of 1.50-1.69 GHz and a 3-dB AR bandwidth of 1.545-1.585 GHz. Moreover, in both modes, the antenna yields a good broadside radiation pattern with a gain of > 6.0 dBic and a radiation efficiency of > 70% across its operational bandwidth.
Keywords: Circularly polarized antennas; Crossed dipoles; Left-hand circular polarizations; Operational bandwidth; Parasitic element; Polarization Switchable; Right-hand circular polarizations; Switchable polarization; Circular polarization; Crossed dipole; Near-field resonant parasitic element; Switchable polarization